Optical Stark effect of exciton in InGaAs/InAlAs oblate spheroidal quantum dots - Lê, Thị Ngọc Bảo; Đinh Như, Thảo (Hue University Journal of Science: Natural Science, 2022)
In this paper, we studied the existence of the exciton optical Stark effect in oblate spheroidal quantum dots by using the renormalized wavefunction theory. A strong pump wave was applied to couple the electron quantization states in the conduction band in a three-level system model. We observed two separate peaks of the interband absorption transitions representing the separation of the electron energy levels due to the optical Stark effect. In addition, the influence of the pump field energy, size, and geometry of the quantum dots on the effect characteristics was also investigated in detail.